The Interplay Between Obesity and Type 2 Diabetes: Common Pathophysiological Mechanisms Contributing to Telomere Shortening - Stella Baliou; Miruna-Maria Apetroaei; Eleftheria Hatzidaki; Sergey V. Kuzmin; Manolis N. Tzatzarakis; Andreea Letiția Arsene; Aristides Tsatsakis; Petros Ioannou (Life)
The worldwide prevalence of obesity continues to increase, representing a serious public health issue due to associated comorbidities. Obesity is associated with type 2 diabetes mellitus (T2D), which shares similar pathophysiological mechanisms. In both conditions, oxidative stress, inflammation, mitochondrial dysfunction, abnormal adipose tissue function, and senescence are observed, ultimately leading to insulin resistance. In both cases, hypertrophic adipose tissue is associated with telomere shortening. Elucidating the mechanisms underlying telomere shortening in obesity and diabetes may be crucial for deepening our understanding of these pathologies, with the ultimate aim of its translational implications. Several studies have shown that telomere shortening is present in patients with metabolic disorders, emphasizing its prognostic value for the onset and progression of these diseases. From this perspective, this article highlights the importance of telomere biology, which can aid in developing new therapeutic options for metabolic disorders.